Mitigation capacity of an eco-friendly locally sourced surfactant for gas hydrate inhibition in an offshore environment - Virtue, Urunwo Elechi; Sunday, Sunday Ikiensikimama; Joseph, Ajienka (Wiley Periodicals, Inc., 2021)
Gas hydrate inhibition is very key and has become more sensitive as oil and gas exploration goes into deeper terrains espe-cially deep oﬀshore as a result of technological advancement. Use of chemicals has been the most eﬃcient and cost eﬀective in these areas. These chemicals add to the cost of doing oil and gas business and also cause harm to the environment; hence, research has been going on for more eco-friendly and cost-eﬃcient inhibitors. This study takes a look at a locally sourced surfactant as one of such inhibitors. Varying weight percentages of the LSS were screened in a locally fabricated laboratory mini ﬂow loop of 39.4m with an internal diameter of 0.5 inch mounted on an external frame work. The various pressure plots (pressure vs. time, change in pressure vs. time, initial and ﬁnal pressures vs. time) show that the LSS used in very small percentages performed better than the synthetic inhibitor methanol (MeOH) used in higher weight percentage than the LSS. The ﬁnal pressures for MeOH for 1–5 wt% were 104, 111, 123, 120 and 123 psi while those of the LSS were 115, 128, 125, 127 and 131 psi, respectively, for 0.01–0.05 wt%, respectively. This means that the system with LSS had more stable pressure values than those of MeOH. Similarly, the change in pressure at the end of 120min for MeOH was 46, 39, 27, 30 and 27 psi against 35, 22, 25, 23 and 19 psi for LSS. This was an indication that more gas was used up in the system with MeOH than in the system with LSS. The mitigation capacity of the LSS in percentage was calculated to be 69.30, 80.71, 78.07, 79.82 and 83.3% for 0.01–0.05 wt% while MeOH had values of 59.65, 65.79, 76.32, 73.68 and 76.32% for 1–5 wt%, respectively. This showed that the LSS inhibited hydrates better than MeOH in all the weight percentages considered. There is need to harness and develop the LSS for gas hydrate mitigation because it performed better than MeOH which is a known toxicant to man, terrestrial and aquatic habitat.
Keywords: Onyewuchi Akaranta; Okon Efiong Okon; Gas hydrate; Locally sourced surfactant; Methanol; Mitigation capacity; Laboratory mini ﬂow loop; STEM; University of Port Harcourt